Socialization of Integrative Thematic Model: Sports Education in Learning English Vocabulary - Nasution, Alwi Fahruzy; Parinduri, Ramadha Yanti; Hasibuan, Siti Aminah; Tarigan, Fatin Nadifa; Ismayani, Ismayani (Universitas Negeri Medan, 2023)
The right learning model is one of the keys to success in learning. The integrative thematic learning model is a model that combines two subjects where in this service activity was carried out the preparation of physical subjects for language teaching, especially foreign languages such as English. This service activity was carried out with the aim of introducing an integrative thematic learning model of physical education in learning English vocabulary so that students can improve their mastery of the language. Located at SD Adhyaksa Medan as an activity partner, assisting in learning English through sports education. The participants in this activity were students who were at the elementary level and carried out using an integrative thematic learning model. Before and after the implementation of the activity, interviews were conducted and the results showed an increase in the participants' interest in learning English vocabulary after being combined with physical activity. Furthermore, the results of the evaluation include the expectation that teachers can develop this learning model in other subjects for variations in teaching.